Studi Reseptor Virus Infectious Bursal Disease (IBD) pada Organ Limfoid Ayam Pasca Vaksinasi dengan Metode Imunohistokimia - Restu Librani; Agus Setiyono; Wiwin Winarsih (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2019)
Infectious bursal disease (IBD) affects economical impact for breeders due to it can cause damage lymphoid organ, especially bursa of Fabricius and causing failure the vaccination program. Infectious bursal disease virus receptors on lymphoid organs suspected contribute to subclinical and clinical IBD incidence in the chickens. The aim of this study was to determine and compare the distribution of IBDvirus receptors on lymphoid organ of the chicken which obtained different IBD vaccination program. The presence of virus receptors in bursa of Fabricius, spleen, and thymus were observed microscopically using immunohistochemical method and evaluated with Image J® software. Monoclonal anti LSCC-BK3 (Gifu University, Japan) antibodies as primary antibody was used in this study. The result showed that IBDvirus receptors found abudantly in the bursa of Fabricius, afterwards in the spleen and thymus. No significant differences of IBD virus receptor distribution within lymphoid organs between chicken which obtained once and twice IBD vaccination. Infectious bursal disease virus receptor distribution in bursa Fabricius chickens aged 23 days received twice IBD vaccination more than once IBD vaccination program.